The aerospace supply chain and cyber security : challenges ahead - Koepsel, Kirsten M., 1953- (Society of Automotive Engineers, 2018)
'The aerospace supply chain and cyber security: challenges ahead' looks at the current state of commercial aviation and cyber security, how information technology and its attractiveness to cyber attacks is affecting it, and the way supply chains have become a vital part of the industry's cyber-security strategy.--Publisher website.
Keywords: Cyber intelligence (Computer security); Aeronautics, Commercial -- Passenger traffic.; Aeronautics, Commercial -- Computer networks -- Security measures.; elektronické knihy; electronic books